2013
DOI: 10.5897/ajfs2013.1029
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effects of two commercial feed additives on growth performance and body composition of African catfish Clarias gariepinus fingerlings

Abstract: An experiment was conducted to evaluate the effect of two commercial feed additives on growth, nutrient utilization and body composition of African catfish, Clarias gariepinus fingerlings. Two commercial feed additives Aqua booster ® and Aqua pro ® were added to the basal diet at 0.5 g kg −1 feed and fed to the fish for 56 days at 3% body weight. Fish fed on diets with commercial feed additives showed significantly improved growth performance, feed utilization and body composition compared to fish fed on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
2
6
0
2
Order By: Relevance
“…From a proximate composition point of view, feed additives increased the level of protein in O. niloticus. The body composition values obtained in this study were similar to those reported by [8,18] using commercial feed additives. Survival of O. niloticus can be improved by feed additives supplementation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…From a proximate composition point of view, feed additives increased the level of protein in O. niloticus. The body composition values obtained in this study were similar to those reported by [8,18] using commercial feed additives. Survival of O. niloticus can be improved by feed additives supplementation.…”
Section: Discussionsupporting
confidence: 78%
“…Recently, some studies show the positive effects of dietary medicinal plants/herbs and feed additives on growth and feed utilization in fish and crayfish [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Work developed in other research corroborates what was obtained in this research, as these authors obtained higher growth rates in the diets that showed the highest protein content (Ogunji and Wirth, 2001;Dada et al, 2013;Adebola et al, 2015;Méndez et al, 2018). Something similar happened for the length and weight gain.…”
Section: Méndez-martínez Et Alsupporting
confidence: 87%
“…The African catfish, a major species for human consumption in many African countries, exhibits high growth performances and important capacities to grow on various rearing conditions. In general, water quality parameters of temperature (27.05°C), dissolved oxygen (5.64 mg.L -1 ), pH (8.04) and total ammonium (0.06) were maintained as recommended for this species (Dada and Olugbemi, 2013;Admassu et al, 2015), and diets were formulas with ingredients, similar to those used in other research (Sogbesan et al, 2006;Adebola et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Globally, there is a great decline in aquaculture production, due to fish feed manufacturers substituting vital feed ingredients with alternative feed stuffs that cannot achieve fish nutritional requirements. One of the critical challenges faced by aquaculture is the high cost of fish feeds and more than 50% of the total cost of production is intensified in culture system (Ali et al, 2004 aquaculture (Dada and Olugbemi, 2013).…”
Section: Introductionmentioning
confidence: 99%